Au‑delà de la frontière binaire du genre : les personnages sculptés recuay (100‑700 apr. J.‑C., sierra nord-centrale du Pérou) - Alexia Moretti (Frontière·s)
Ancient societies of the New World have frequently been observed through a binary and invariable system of sex and gender because studied and understood through conceptual schemes based on ethnocentric models of the Old World. However, it has become a commonplace in pre‑Hispanic studies to recognize that many ancient and ethnographically documented Native American societies perceive sex and gender in a more open and mutable way, as a continuum of possibilities that overstep the boundary of binary gender. Scholars are thus invited to reflect more on the possibilities offered by this fluid and dynamic conception of gender and to include those possibilities in their studies for the restitution of past societies that is more in line with the pre‑Hispanic system of thought. This is precisely the aim of this study on anthropomorphic stone sculptures belonging to the Recuay pre‑Hispanic Andean tradition. This contribution questions how this gender fluidity occurs in the iconography of the Recuay sculptures to allow a better comprehension of the essence of the carved figures.